Survey of discontinuities and evaluation of the slope stability at Mangueirão mine - Paz, Valmor Madeira (2015)
The study and control of slope stability have grown greatly in recent decades, so the quality and the reliability of the results of an analysis of stability are very important because they provide savings for the enterprise and security for workers. This article aims to address the geological and geotechnical aspects considered most important for the stability of slope excavation in rock masses. To achieve this goal, a review of the characteristics of discontinuities was held as spacing, orientation, opening, filling, percolation and roughness fractures. Through scanlines, was made histogram frequency of these discontinuities, stereographic projections in the software stereonet9 and identification of the main families of discontinuities, because the main determinants of failure modes in rock masses are these structures. To do so, seven slopes were selected, with evidence of instability, which were subjected to a series of field studies to obtain the parameters necessary to reach the minimum safety factor. In this way situations were simulated eight 45 ° intervals with mining advance, that in three of them were obtained satisfactory results, given the expectation of work.